ANEMIA AND CARDIOVASCULAR DISEASES DURING PREGNANCY: DIAGNOSIS, MANAGEMENT, AND GP TACTICS - Xusanova Shakhrizoda Sherzod qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the impact of anemia and cardiovascular diseases during pregnancy on the female body, their diagnosis, management strategies based on modern approaches, and the role of the General Practitioner (GP). Pregnancy is a period marked by significant physiological changes, during which preexisting chronic diseases may worsen or new pathological conditions may emerge. In particular, cardiovascular and hematological disorders pose serious risks to maternal and fetal health. The article highlights practical recommendations for clinical case management, modern diagnostic capabilities, and the primary care role of GPs in ensuring maternal and fetal well-being.